2022
DOI: 10.2147/ccide.s346743
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Digital Workflow Planning for Maxillary Teeth Restoration with Porcelain Laminate Veneers: A Clinical Report

Abstract: Nowadays, media-influenced patients have the desire to “extremely rapidly” alter their teeth to “ideal” and “too bright” ones. Although some esthetically demanding cases need to be thoroughly planned and treated through prolonged phases, other cases can be handled quickly. In such cases, we can witness the impact of many computer software programs for digital smile design that have penetrated clinical practice. This clinical report describes a conventional and digital step-by-step treatment workflow for restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Additionally, transferring data from the virtual design to the stone model poses challenges and opportunities for potential error [17]. Alshali and Asali (2022) showed that digital smile design using two different software packages and feldspathic porcelain for restoring anterior maxillary teeth with porcelain laminate veneers demonstrates an effective and predictable workflow, leading to adequate esthetic results as compared to the conventional workflow [24]. The significance of this particular case is that the authors and patient agreed that the conventional technique yielded better results.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, transferring data from the virtual design to the stone model poses challenges and opportunities for potential error [17]. Alshali and Asali (2022) showed that digital smile design using two different software packages and feldspathic porcelain for restoring anterior maxillary teeth with porcelain laminate veneers demonstrates an effective and predictable workflow, leading to adequate esthetic results as compared to the conventional workflow [24]. The significance of this particular case is that the authors and patient agreed that the conventional technique yielded better results.…”
Section: Discussionmentioning
confidence: 99%
“…When using traditional prosthetic dental treatment methods to provide smile esthetics, communication between the patient and the clinician is limited, and the results depend on the laboratory process. 1 Today, the development of digital technologies allows the clinician to analyze the patient's current situation and digitally design the smile to be made and visualize the results in advance. In this way, the communication between the patient and the clinician improves, and the results of the prepared smile design become more predictable.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the communication between the patient and the clinician improves, and the results of the prepared smile design become more predictable. 1,2 The dominant components that make up the smile are the upper anterior incisors. After that, the gums, lips and other facial structures form the components of the smile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation